Effect of side edge angle and effective rake angle on top burrs in micro-milling - Saptaji, Kushendarsyah (2013)
Experimental investigations on the effect of side wall edge strengthening, to reduce top burr formation, in micro-milling slots in Al-6061 alloy using a carbide tool are reported here. The side edge is strengthened by increasing the edge angle to a value higher than the usual 90°. Side edge angle is varied in two ways: one, by changing the work geometry and two, by introducing a taper into the milling tool. The burrs formed are examined qualitatively in a scanning electron microscope and quantitatively using a surface profiler. The analysis of the results shows that top burrs are reduced both by strengthening the side edge and also by the effect of the taper angle in the micro-milling tool. The effect of the side edge angle in the tool can be attributed to the edge strengthening. On the other hand, an analysis of the tapered tool geometry indicates that the velocity rake, normal rake and effective rake angles increase with the taper angle and can hence explain the observed burr reductions.